2004
DOI: 10.1111/j.1445-1433.2004.03266.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of intraoperative frozen section in the management of thyroid nodules

Abstract: The present review found little benefit in performing intraoperative frozen section in this setting. As a diagnostic test the cost of frozen section (NZ $200 for each frozen section) needs to be weighed against its low clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…One study reported a decrease in the number of reoperations as a result of routine FS analysis, which led to an estimated saving of 40% [5]. Since the costs of both FS analysis and operative intervention differ greatly between countries [5,10,26], we believe that this issue needs individualization for each country. There is limited information available regarding the clinical and cost results of FS in thyroid cancer in Turkey.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…One study reported a decrease in the number of reoperations as a result of routine FS analysis, which led to an estimated saving of 40% [5]. Since the costs of both FS analysis and operative intervention differ greatly between countries [5,10,26], we believe that this issue needs individualization for each country. There is limited information available regarding the clinical and cost results of FS in thyroid cancer in Turkey.…”
Section: Discussionmentioning
confidence: 96%
“…Although there are many reports concerning FS in thyroid surgery, the role of intraoperative FS in thyroidectomy is still a subject of controversy. On one hand there is strong evidence that FS diagnosis is accurate for processing a high volume of surgical pathology cases and may avoid surgical overand under-treatments and the need for a second operation [5,9,11,12], while on the other hand it is believed that the role of FS is becoming increasingly limited and has no substantial benefit in patient outcome [4,10,13]. One of the main goals of intraoperative FS is to identify which patient has malignancy, to avoid the increased costs and operative risks associated with a completion surgery [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of the intra-operative frozen section (FS) remains controversial while its potential to help the surgeon decide between hemithyroidectomy or total thyroidectomy. The method can potentially avoid a second surgery to remove the contralateral lobe should the surgical specimen reveal malignancy in the histopathology included in paraffin and, alternatively, it can avoid an unnecessary total thyroidectomy which will cause the patient to have to replace levothyroxine forever and increase the chance of the patient developing hypoparathyroidism and damage to the recurrent laryngeal nerve 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In case of malignancy total thyroidectomy should be the option of surgical choice in order to protect patient from the risk of a second intervention which might possess increased morbidity and complication rates. On the other hand, according to the accurate diagnosis of a benign thyroid disease the impact of FS could alter operative management from aggressive to conservative surgery [4][5][6].…”
Section: Introductionmentioning
confidence: 99%